2012
DOI: 10.1007/s11682-012-9160-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation correlates with the functional connectivity of the anterior cingulate cortex in patients with multiple sclerosis

Abstract: We investigated how resting state (RS) functional connectivity (FC) of the anterior cingulate cortex (ACC) correlates with cognitive rehabilitation in relapsing remitting multiple sclerosis (RRMS) patients. A neuropsychological assessment and RS fMRI at baseline and after 12 weeks were obtained from 20 RRMS patients, who were assigned randomly to undergo treatment (n = 10) (treatment group-TG), which entailed computer-assisted cognitive rehabilitation of attention/information processing and executive functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 38 publications
5
82
0
Order By: Relevance
“…In the control group, a decreased RS FC between the ACC and the right cerebellum and right inferior temporal gyrus (ITG) was detected. 3 A recent neuropsychological re-assessment of these patients showed that the positive effect on neuropsychological performance was still detectable six months after treatment termination and resulted in an improvement measured on quality of life and depression scales. 11 The aim of this study was to investigate the relationship between fMRI changes observed during the rehabilitation period, and neuropsychological performance at six-month follow-up.…”
Section: Introductionmentioning
confidence: 98%
“…In the control group, a decreased RS FC between the ACC and the right cerebellum and right inferior temporal gyrus (ITG) was detected. 3 A recent neuropsychological re-assessment of these patients showed that the positive effect on neuropsychological performance was still detectable six months after treatment termination and resulted in an improvement measured on quality of life and depression scales. 11 The aim of this study was to investigate the relationship between fMRI changes observed during the rehabilitation period, and neuropsychological performance at six-month follow-up.…”
Section: Introductionmentioning
confidence: 98%
“…21 Pa-tients with MS show differences in both the pattern and magnitude of fcMRI values, and there is some indication that these changes are related to the level of disease burden and cognitive deficits. 20,[22][23][24][25][26] In particular, connectivity between the posterior cingulate and other structures in the default mode network has shown a relationship with cognition. 23,27 It is unclear whether fcMRI values are affected by sex.…”
mentioning
confidence: 99%
“…Subsequently, the same research group investigated how resting state functional connectivity (FC) of anterior cingulated cortex correlates with cognitive training. At follow-up, the anterior cingulum showed an increased FC with the right inferior parietal lobule and decreased FC with the right inferior temporal gyrus in the treated group only; some of these FC modifications significantly correlated to enhanced PASAT scores after the training [79].…”
Section: Cognitive Rehabilitationmentioning
confidence: 85%